Learning Analytics: a Metacognitive Tool to Engage Students Research study - Volungevičienė, Airina (De Gruyter, 2021)
The research described in this book searches for the answers on how learners learn in todays open and networked learning environments and how learners, educators, institutions, and researchers can best support this process. There is sufficient data available on virtual learning environments, provided by learning analytics, on student and teacher behaviour and performance, but there is no common practice among teachers in higher education for using this data to improve the learning and teaching process. Learning analytics and data may inform and improve open and online learning from the point of view of teacher and learner awareness about their behaviour and their learning and teaching methods. The idea of describing learning analytics as a metacognitive tool, suggesting a development of metacognitive decision-making skills in teacher education, and focusing on learning design in higher education by using data from learning analytics served as the main focus of this research. The aim of the research was to create the model of application of learning analytics method as a metacognitive tool to enhance student success. The aim of the research was reached through theoretical and empirical objectives, namely: describing the learning analytics method as a metacognitive tool revealing teacher metacognitive practices in application of learning analytics in teaching and learning, as well as learning design and creating the model of application of learning analytics as a metacognitive tool to enhance student success. This research study is the result of the research project "Open Online Learning for Digital and Networked Society (3.3-LMT-K-712-01-0189)".